Camberwell Mill : Copied, by permission, from Mr. Blanch's History of Camberwell. - Prior, William Henry (Tufts Archival Research Center, 2006)
This illustration is from Edward Walford "Old and new London, a narrative of its history, its people, and its places, vol. 6" From Ye parish of Camerwell : a brief account of the parish of Camberwell : its history and antiquities.